Essay on Exoticism : An Aesthetics of Diversity - Segalen, Victor, 1878-1919 (Book collections on Project MUSE., 2002)
A series of notes on alterity written by Victor Segalen between 1904 and 1918, and here translated into English for the first time, anticipates the post-colonial critique of colonial theory.